Financial Performance and Operational Efficiency: A Financial Ratio and Value-for-Money Analysis - Sunardi Perastia; Eka Desy Purnama (Global Academy of Business Studies, 2026)
Purpose: This study aims to evaluate the financial performance of RS UKRIDA, a private teaching hospital, using financial ratio analysis and the Value for Money (VfM) approach. The evaluation is crucial for assessing the hospital’s financial management, considering its dual role as a healthcare provider and an educational institution. Research methodology: A quantitative descriptive approach is employed, analyzing RS UKRIDA's financial statements (income statement, balance sheet, and budget realization reports) for the 2023–2024 period. Financial ratios assess liquidity, solvency, profitability, and activity, while the VfM approach evaluates economy, efficiency, and effectiveness in financial management. Results: The study finds that RS UKRIDA shows efficient budget utilization, but economic and effectiveness aspects need improvement, particularly in budget control and revenue target achievement. Financial ratios reveal weak liquidity and solvency, and negative profitability, though some improvement is observed during the study period. Conclusions: RS UKRIDA exhibits operational efficiency but lacks financial stability and optimal revenue realization. The combination of financial ratio analysis and VfM provides a comprehensive view, indicating the need for a balanced approach to improve financial performance. Limitations: The study is limited by its focus on a single institution and its reliance on secondary financial reports, which may not fully capture non-financial aspects of performance. Contribution: This research offers valuable insights for RS UKRIDA’s management in improving financial performance and provides an academic reference for future studies on financial management in private teaching hospitals.